Sarcoidosis and burn pit exposure in military deployers to Iraq, Afghanistan, and Southwest Asia: Sarcoidosis in military personnel - Patel, Divya; Jaber, Johnny; Loso, Jennifer; Perera, Hassan; Daouk, Salim; Innabi, Ayoub; Gomez-Manjarres, Diana; Krefft, Silpa; Miller, Robert (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Inhalational exposures have been hypothesized to play a role in the pathogenesis of sarcoidosis. Herein, we describe a cohort of US Military personnel diagnosed with sarcoidosis during or after deployment to Southwest Asia and Afghanistan, who experienced complex inhalational exposures to burn-pits and desert dust. Methods: Consecutive military personnel at four sub-specialty clinics across the United States were screened for deployment to Southwest Asia and Afghanistan and diagnosis of sarcoidosis based on 1999 ATS/ERS/WASOG Statement on Sarcoidosis. Detailed demographic, deployment and exposure data was collected. The data combined was analyzed after de-identification and local IRB approval. Results: Twenty-one patients met our case definition. Seventeen patients were male and 62% had extrapulmonary involvement, including 38% with musculoskeletal involvement. Conclusions: Our study suggests that the sarcoidosis in military personnel to Southwest Asia can be diagnosed many years after deployment. To our knowledge, this is the first case series to describe a group of military personnel diagnosed with sarcoidosis and exposures specific to military deployment to Southwest Asia.